ANALISIS PERILAKU DAN MOTIVASI SERTA PERANAN PSIKOLOGI DALAM TINDAK PIDANA TERORISME - Lestari, Neng Aini Sri Sunda; Tusyadiah, Hapifah; Purwati, Siti Ayu Resa; Hosnah, Asmak Ul (LPPM Universitas Bina Bangsa, 2024)
The crime of terrorism is a complex phenomenon that requires a deep understanding of behavior, motivation and the role of psychology in its context. Analysis of terrorist behavior highlights a complex process of radicalization, in which individuals are exposed to extreme thinking and intensive indoctrination processes. The motivation behind acts of terrorism involves factors such as political or religious ideology, dissatisfaction with the government, and the drive to gain recognition or praise. Meanwhile, psychology plays an important role in understanding the dynamics of individuals or groups in committing acts of terrorism, including psychological factors such as the need for identity, environmental influences, cognitive and emotional processes, as well as responses to past traumatic experiences. With a deep understanding of these aspects, measures to prevent and counter terrorism can be designed more effectively, through a holistic and coordinated approach between national security, education, social development and psychological intervention